Seafood consumption and blood cadmium level of respondents along the coastal area of Melaka, Malaysia - Md Zulkifli, Hamizah; Mohd Elias, Saliza; Aris, Ahmad Zaharin; Abu Bakar @ Jamaludin, Suhaili; Mohd Noor, Farrah Atiqah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Eating seafood has become a major health concern for many people due to the present of heavy metal especially cadmium (Cd). Cd can accumulate in the body and disrupt the normal cellular processes which will eventually lead to organ damage. This study aims to determine the seafood consumption pattern and blood cadmium (BCd) as well as the association between these two variables among respondents living along the coastal area of Melaka. Methods: Pretested questionnaires were used to collect background and food frequency intake from coastal villagers through convenient sampling method. Venous blood samples were analysed by using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) for BCd determination. Results: A total of 63 respondents who 54% were female with median age of 34 years old provided complete data in this study. The most frequently consumed seafood and its product were shrimp paste (31.5%) followed by mackerel (13.6%), hardtail-scad (6.2%), flatfish (4.5%) and fish ball (4.0). All blood samples showed the present of Cd with median (IQR) = 0.076 (0.1) μg/L and ranged between 0.007 to 1.284 μg/L. The finding showed no association between frequently consumed seafood and low BCd of the respondents. On the other hand, gender was found to be significantly associated with the BCd. Conclusion: Seafood consumption pattern was not significantly associated with BCd which suggests that frequent seafood consumption may not contribute much to BCd level among the respondents as well as it may indicates safe consumption of these seafood available in the study location.